2016
DOI: 10.1158/0008-5472.can-15-1965
|View full text |Cite
|
Sign up to set email alerts
|

Inherent and Tumor-Driven Immune Tolerance in the Prostate Microenvironment Impairs Natural Killer Cell Antitumor Activity

Abstract: The field of immunotherapy for solid tumors, such as prostate cancer, has been recently focusing on therapies that can counter tumor-mediated immunosuppression. Precise quantification and characterization of the immune infiltrates in tumors is crucial to improve treatment efficacy. Natural killer (NK) cells, major components of the antitumor immune system, have never been isolated from prostate tumors, despite their suspected role in disease progression. Here, we examined the frequency, phenotype, and function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
135
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 51 publications
5
135
0
4
Order By: Relevance
“…In this study, we focused on the role of intracellular IL‐6 signaling in developing the resistance of PCa cells to NK cell‐mediated cytotoxicity. It was previously suggested that an immunosuppressive environment impairs NK cell function at multiple levels in PCa (Pasero et al ., ). IL‐6 can be secreted by other types of cells in the tumor microenvironment (TME) including macrophages, endothelial cells, and bone marrow mesenchymal cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, we focused on the role of intracellular IL‐6 signaling in developing the resistance of PCa cells to NK cell‐mediated cytotoxicity. It was previously suggested that an immunosuppressive environment impairs NK cell function at multiple levels in PCa (Pasero et al ., ). IL‐6 can be secreted by other types of cells in the tumor microenvironment (TME) including macrophages, endothelial cells, and bone marrow mesenchymal cells.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the upregulation of PD‐L1, the downregulation of NKG2D‐activating ligands such as UL16 binding protein 1 (ULBP1), ULBP2, ULBP3, major histocompatibility complex class I chain‐related molecules A and B (MICA and MICB) was reported to be another pathway for tumor cells to escape from NK cell‐mediated cytotoxic actions (Nausch and Cerwenka, ). It was also suggested that the downregulated NKG2D in NK cells prevented NK cell recognition by tumor cells (Pasero et al ., ). In addition, Liu et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, recent detection of tissue tolerance mechanisms against NK cells further implicates the presence of a strong immunosuppressive environment in PCa. For instance, NK cells infiltrating the prostate gland display an immature phenotype with low or no cytotoxic potential, and PCa cells may also induce the expression of NK inhibitory receptors and downregulate the expression of NK activating receptors [71]. The function of mast cells (MCs) in mPCa is clearly determined by the microenvironment.…”
Section: Microenvironmental Regulation Of Pca Metastasismentioning
confidence: 99%
“…A high level of NK cell infiltration correlates with a favourable prognosis in numerous cancer types . However, the immunosuppressive tumour microenvironment can also impair NK cell cytotoxicity by increasing the numbers of MDSCs or other immunosuppressive cells .…”
Section: Mechanisms Of Tumour Immune Evasionmentioning
confidence: 99%